2019
DOI: 10.1042/cs20190067
|View full text |Cite
|
Sign up to set email alerts
|

Specialized pro-resolving mediators in diabetes: novel therapeutic strategies

Abstract: Diabetes mellitus (DM) is an important metabolic disorder characterized by persistent hyperglycemia resulting from inadequate production and secretion of insulin, impaired insulin action, or a combination of both. Genetic disorders and insulin receptor disorders, environmental factors, lifestyle choices and toxins are key factors that contribute to DM. While it is often referred to as a metabolic disorder, modern lifestyle choices and nutrient excess induce a state of systemic chronic inflammation that results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 231 publications
0
8
0
Order By: Relevance
“…Notably, pro-resolving mediators, derived from polyunsaturated fatty acids, accelerate the treatment of inflammatory diseases(86), including murine models of diabetes(87) and patients with metabolic syndrome(88).Hyperglycemia and dyslipidemia in T1D are associated with an increased inflammatory state in the monocytes/macrophages, resulting in increased NO production via the NLRP3/iNOS pathway, upregulated expression of proinflammatory cytokines and chemokine receptors and augmented glycolytic activity. In conclusion, since the ex-vivo treatment with DHA abolished the T1D-induced changes and attenuated the inflammatory state of the PMs, DHA supplementation may represent a promising adjunct therapy for treating T1D patients.…”
mentioning
confidence: 99%
“…Notably, pro-resolving mediators, derived from polyunsaturated fatty acids, accelerate the treatment of inflammatory diseases(86), including murine models of diabetes(87) and patients with metabolic syndrome(88).Hyperglycemia and dyslipidemia in T1D are associated with an increased inflammatory state in the monocytes/macrophages, resulting in increased NO production via the NLRP3/iNOS pathway, upregulated expression of proinflammatory cytokines and chemokine receptors and augmented glycolytic activity. In conclusion, since the ex-vivo treatment with DHA abolished the T1D-induced changes and attenuated the inflammatory state of the PMs, DHA supplementation may represent a promising adjunct therapy for treating T1D patients.…”
mentioning
confidence: 99%
“…As a new therapeutic method in many acute and chronic inflammatory diseases, Specialized pro-resolving mediators (SPMs).has become a research hotspot (Fullerton and Gilroy, 2016). Low levels of circulating SPMs in DM patients give this population the potential to be treated with SPMs (Spite et al, 2014;Brennan et al, 2019). SPMs promote PMNs clearance, inflammation regression, and epithelial tissue repair (Quiros and Nusrat, 2019), local injection of Resolvin D1 (RvD1).in DW can correct the phagocytosis functional defects of Mp, clearance of apoptotic PMNs, and promote wound healing (Tang et al, 2013).…”
Section: Mechanism Of Inflammationmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a chronic metabolic, endocrine disease characterized by persistent hyperglycemia. Chronic complications are its main hazards, often involving microvessels, large vessels, and the nervous system, resulting in heart, brain, kidney, and other essential organ lesions (Brennan et al, 2019;Tellechea et al, 2020). Besides, peripheral vascular and neuropathy lesions are often combined with pathogenic microbial infections to cause diabetic foot disease.…”
Section: Introductionmentioning
confidence: 99%
“…DR, as a serious and speci c neurovascular complication of DM, remains the leading cause of vision loss and preventable blindness in adults aged 20-74 years [4][5][6] . Many studies have implicated that chronic in ammation plays an important role in insulin resistance and DM development [1,7,8] . Moreover, accumulated evidence has shown that in ammation also plays a key part in the development and progression of DR [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%